Ethics in quality - Mundel, August B. (Marcel Dekker, 1991)
This on-the-job guide poses essential questions regarding the best action to take when dealing with a company, an the verge of adopting or, which had adopted a course of action that may lead it to act in an "irresponsible" manner--offering case studies in which readers can compare their answers against those given in the examples.